The effect of lifestyle modification on metabolic, anthropometric parameters and hirsutism score in polycystic ovary syndrome - Nur Intan, Yulice Soraya; Reza, Hanif; Gunawan, Robby (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2022)
Polycystic ovary syndrome (PCOS) is a hormonal disorder that affects women of reproductive age. It is characterised by several clinical signs and symptoms, including hyperandrogenism, ovarian dysfunction, and chronic anovulation. Obesity and hormonal imbalances can be reduced in PCOS by modifying lifestyle habits. The effects of lifestyle changes on PCOS were investigated, and it was found that consuming less fat and engaging in physical activity reduced metabolic disturbances. The purpose of this study was to examine the effects of lifestyle modifications on metabolic parameters, anthropometric parameters, and the hirsutism score as they relate to the pathogenesis of PCOS. This study involved a total of 10 patients diagnosed with PCOS at the Sultan Agung Semarang Islamic Hospital. Blood glucose, triglycerides, HDL (high density lipoprotein), blood pressure, waist circumference, hirsutism score, and vital sign data related to PCOS were measured before and after a 4-month treatment. PCOS patients' fasting blood sugar levels, triglycerides (TG), high density lipoprotein (HDL), hirsutism scores, blood pressure (systolic and diastolic), and waist circumference averaged 92, 60; 48.10; 96.90; 10.5; 121.5/77; 86.80, respectively, at baseline (pretreatment). After four months of treatment, the average levels of fasting blood sugar, triglycerides, high-density lipoproteins, blood pressure (systolic and diastolic), hirsutism scores, and waist circumference were 108.7, 50, 99.8, 7, 122.3, 82.7, and 87.50, respectively. Changes in lifestyle led to significant variations in fasting blood sugar levels as a metabolic parameter and hirsutism scores, but not in triglycerides, high-density lipoprotein, waist circumference, or blood pressure.